Social Media Campaign: Thrifting sebagai Pencegahan Limbah Tekstil Fast Fashion - Ayu Dear Pangesti; Bernadet Cahyanintyas A; Ria Mareta Yulfan; Tutut Chusniyah (Flourishing Journal, 2023)
Indonesia is the fourth most populous country, as one of the biggest waste contributors in the world. Textile waste itself has become a serious problem, around 2.3 million tons of fabric waste will be collected in 2021. Therefore, a thrifting campaign has been carried out as an effort to tackle this textile waste. With the hope that thrifting can minimize the amount of existing textile waste. The campaign was carried out on social media for one week by distributing posters about the dangers of fast fashion for the environment and thrifting as a solution to textile waste. This program is evaluated based on the number of likes, number of viewers, and testimonials given by viewers. Based on the comments, it can be seen the target's response to this program. This response is used as material for program evaluation. In conclusion, there are still many people who do not know the use of thrifting for the environment, especially as a reduction of textile waste.Abstrak Indonesia merupakan negara dengan penduduk terbanyak keempat, sebagai salah satu penyumbang sampah terbesar di dunia. Sampah tekstil sendiri sudah menjadi permasalahan yang serius, sekitar 2,3 juta ton limbah kain terkumpul di tahun 2021. Oleh karenanya dilakukan kampanye mengenai thrifting sebagai upaya dari penanggulangan limbah tekstil tersebut. Dengan harapan thrifting dapat meminimalisir jumlah sampah tekstil yang ada. Kampanye dilakukan pada sosial media selama satu minggu dengan menyebarkan poster mengenai bahaya fast fashion untuk lingkungan dan thrifting sebagai solusi dari limbah tekstil. Program ini dievaluasi didasarkan pada jumlah like, jumlah viewer, dan testimoni yang diberikan oleh para viewer. Berdasarkan komentar-komentar dapat diketahui respon target terhadap program ini. Respon ini digunakan sebagai bahan evaluasi program. Kesimpulannya masih banyak masyarakat yang belum mengetahui kegunaan thrifting untuk lingkungan terutama sebagai pengurangan limbah tekstil.